Kajian Teologis Terhadap Otoritas Ibu dalam Peran Membentuk Karakter Anak pada Keluarga Batak - Siagian, Riris Johanna; Siburian, Elfrida (SEKOLAH TINGGI TEOLOGI STAR'S LUB LUWUK BANGGAI, 2022)
This research aims to study from the perspective of Christian theology the concept of Batak culture regarding the authority of women as mothers in forming excellent characters in Batak families. The method used is qualitative. The research was conducted in Pematangsiantar in November-December 2022 with four informants. Two of them are female Batak leaders in the church and theological schools; the other two are youths from Batak families. This study found three roles of mothers who have authority in forming excellent characters in children. The three roles are sipartangiang (prayer), educating children to pray diligently, parsonduk bolon (preparing food needs), educating children to assume responsibility for life together, Ina Soripada (respectable mother), educating children to be polite, honest, and with integrity. Through these three roles, it appears that Batak mothers have the authority to carry out excellent character education for children. It is proven that children from families with such mothers have excellent characters that differ from their peers.